Identifying New/Emerging Psychoactive Substances at the Time of COVID-19; A Web-Based Approach - Catalani, Valeria; Arillotta, Davide; Corkery, John Martin; Guirguis, Amira; Vento, Alessandro; Schifano, Fabrizio (Frontiers in Psychiatry, 2021)
COVID-19-related disruptions of people and goods’ circulation can affect drug markets, especially for New Psychoactive Substances (NPS). Drug shortages could cause a change in available NPS, with the introduction of new, unknown, substances. The aims of the current research were to use a web crawler, NPSfinder®, to identify and categorise emerging NPS discussed on a range of drug enthusiasts/psychonauts’ websites/fora at the time of the pandemic; social media for these identified NPS were screened as well. The NPSfinder® was used here to automatically scan 24/7 a list of psychonaut websites and NPS online resources. The NPS identified in the time-frame between January-August 2020 were searched in both the EMCDDA/UNODC databases and on social media (Facebook, Twitter, Instagram, Pinterest and YouTube) as well, with a content qualitative analysis having been carried out on reddit.com. Out of a total of 229 NPS being discussed at the time of the pandemic, some 18 NPS were identified for the first time by the NPSfinder®. These included: 6 cathinones, 6 opioids, 2 synthetic cannabinoid receptor agonists (SCRAs), 2 PCP-like molecules, 2 psychedelics. Of these NPS, 10 were found to be previously unreported to either the UNODC or the EMCDDA. Out of these 18 NPS opioids and cathinones were the most discussed on social media/reddit, with the highest number of threads associated. Current findings may support the use of both automated web crawlers and social listening approaches to identify emerging NPS; the pandemic-related imposed restrictions may somehow influence the demand for specific NPS classes.